2012
DOI: 10.48550/arxiv.1202.3188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clustering assortativity, communities and functional modules in real-world networks

Lovro Šubelj,
Marko Bajec

Abstract: Complex networks of real-world systems are believed to be controlled by common phenomena, producing structures far from regular or random. Clustering, community structure and assortative mixing by degree are perhaps among most prominent examples of the latter. Although generally accepted for social networks, these properties only partially explain the structure of other networks. We first show that degree-corrected clustering is in contrast to standard definition highly assortative. Yet interesting on its own,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 84 publications
(176 reference statements)
0
4
0
Order By: Relevance
“…2 The networks each exhibit clustering assortativity (signalled by r C > 0). This is also a common feature of realworld networks, both social and non-social [27]. In Ref.…”
Section: A Individual Major Sagasmentioning
confidence: 88%
See 2 more Smart Citations
“…2 The networks each exhibit clustering assortativity (signalled by r C > 0). This is also a common feature of realworld networks, both social and non-social [27]. In Ref.…”
Section: A Individual Major Sagasmentioning
confidence: 88%
“…It has been suggested that networks other than real social networks tend to be disassortatively mixed by degree [6]. Real-world networks are also found to have high clustering assortativity r C and it has been suggested that this also indicates the presence of communities [27].…”
Section: Complex Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…This data can be accessed via [50]. 8) Guava [51]: Guava library dependencies is a network of software dependencies in Guava r07 core libraries. Nodes represent libraries, and a directed link indicates a dependency of one library on another.…”
Section: A Data Descriptionmentioning
confidence: 99%